Magneto-optical studies of the correlation between interface microroughness parameters and the photoluminescence line shape in GaAs/Ga0.7Al0.3As quantum wells - Oliveira, José Brás Barreto de [UNESP]; Meneses, E. A.; Da Silva, E. C F (American Physical Society (APS), 1999)
In this work we analyze the relation between the interface microroughness and the full width at half maximum (FWHM) of the photoluminescence (PL) spectra for a GaAs/Ga0.7Al0.3As multiple quantum well (QW) system. We show that, in spite of the complex correlation between the microscopic interface-defects parameters and the QW optical properties, the Singh and Bajaj model [Appl. Phys. Lett. 44, 805 (1984)] provides a good quantitative description of the excitonic PL-FWHM. ©1999 The American Physical Society.